Development of hyperdynamic circulation and response to β‐blockers in compensated cirrhosis with portal hypertension. Issue 1 (26th November 2015) - Villanueva, Càndid; Albillos, Agustín; Genescà, Joan; Abraldes, Juan G.; Calleja, Jose L.; Aracil, Carles; Bañares, Rafael; Morillas, Rosa; Poca, María; Peñas, Beatriz; Augustin, Salvador; Garcia‐Pagan, Joan Carles; et al.
Abstract : Nonselective β‐blockers are useful to prevent bleeding in patients with cirrhosis and large varices but not to prevent the development of varices in those with compensated cirrhosis and portal hypertension (PHT). This suggests that the evolutionary stage of PHT may influence the response to β‐blockers. To characterize the hemodynamic profile of each stage of PHT in compensated cirrhosis and the response to β‐blockers according to stage, we performed a prospective, multicenter (tertiary care setting), cross‐sectional study. Hepatic venous pressure gradient (HVPG) and systemic hemodynamic were measured in 273 patients with compensated cirrhosis before and after intravenous propranolol (0.15 mg/kg): 194 patients had an HVPG ≥10 mm Hg (clinically significant PHT [CSPH]), with either no varices (n = 80) or small varices (n = 114), and 79 had an HVPG >5 and <10 mm Hg (subclinical PHT). Patients with CSPH had higher liver stiffness ( P < 0.001), worse Model for End‐Stage Liver Disease score ( P < 0.001), more portosystemic collaterals ( P = 0.01) and splenomegaly ( P = 0.01) on ultrasound, and lower platelet count ( P < 0.001) than those with subclinical PHT. Patients with CSPH had lower systemic vascular resistance (1336 ± 423 versus 1469 ± 335 dyne · s · cm ‐5, P < 0.05) and higher cardiac index (3.3 ± 0.9 versus 2.8 ± 0.4 L/min/m 2, P < 0.01). After propranolol, the HVPG decreased significantly in both groups, although the reduction was greater in those with CSPH (‐16 ± 12% versus ‐8 ± 9%, P < 0.01). The HVPG decreased ≥10% from baseline in 69% of patients with CSPH versus 35% with subclinical PHT ( P < 0.001) and decreased ≥20% in 40% versus 13%, respectively ( P = 0.001). Conclusion : Patients with subclinical PHT have less hyperdynamic circulation and significantly lower portal pressure reduction after acute β‐blockade than those with CSPH, suggesting that β‐blockers are more suitable to prevent decompensation of cirrhosis in patients with CSPH than in earlier stages. (Hepatology 2016;63:197–206)